The Prophylactic Use of Remifentanil for Delayed Extubation After Elective Intracranial Operations: a Prospective, Randomized, Double-Blinded Trial. Issue 3 (July 2017) - Wu, Yuan-Xing; Chen, Han; Li, Qian; Hao, Jing-Jing; Zhao, Li-Hong; He, Xuan; Sun, Xiu-Mei; Xu, Ming; Zhou, Jian-Xin
Abstract : Background: Endotracheal extubation is a painful and stressful procedure. The authors hypothesized that the prophylactic use of remifentanil would attenuate the pain intensity and stress responses resulting from extubation in neurosurgical patients. Materials and Methods: In this prospective, randomized, double-blinded, controlled trial, 160 patients with planned delay extubation after elective intracranial operation were randomized 1:1 to receive either remifentanil or normal saline (control) before their extubation. The dose regime of remifentanil was a bolus of 0.5 μg/kg over 1 minute, followed by a continuous infusion of 0.05 μg/kg/min for 20 minutes. The primary outcome was the incidence of severe pain during the periextubation period. Secondary outcomes included changes in the pain intensity and vital signs, failing to pass an extubation evaluation after the study drug infusion, severe adverse events, postextubation complications, and clinical outcomes. Results: Two patients in the remifentanil group did not pass the extubation evaluation. The incidence of severe pain during the periextubation period was significantly lower in the remifentanil group compared with the control group (25.0% vs. 41.3%, P =0.029). Compared with the control group, the visual analog scale in the remifentanil group was significantly lower after the bolus of remifentanil (12±18 vs. 25±27, P =0.001) and immediately after extubation (19±25 vs. 34±30, P =0.001). There were no significant differences in the vital signs immediately after extubation between the 2 groups ( P >0.05). Conclusions: The prophylactic use of remifentanil decreases the incidence of severe pain. Our preliminary findings merit a larger trial to clarify the effect of the prophylactic use of remifentanil on clinical outcomes and adverse events.